Inseminasi Buatan Dalam Perspektif Yusuf Al Qordlowi - Sapri Ali (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2020)
Facing the social development of modern society that raises new legal problems, we need a method of determining the law that can answer new legal problems. Establishment of laws on contemporary issues is not enough to rely on and restore the problem to the Qur'an and Sunnah, because it must be recognized that the Qur'an only contains some detailed laws, while the Sunnah is limited to cases that occur during Rasulullah SAW, then to solve new problems, ijtihad is needed. The purpose of Islamic law (maqashid al-shari'ah) in establishing the law includes maintaining the benefit of religion, soul, reason, progeny and property.In his description, Al-Qardlawi explained that putting another man's water in a deliberate manner in a field where there is no shari'ah bondage 'protected by sharia law' would therefore include adultery because the essence is one and the result is also one. If there are no restrictions in the form of violations of the law, of course, the law of artificial insemination includes adultery that has been determined by sharia law 'and the sentence is stipulated in the Qur'an